Unobserved individual and firm heterogeneity in wage and tenure functions: evidence from German linked employer-employee data - Cornelissen, Thomas; Hübler, Olaf (Bonn, 2007)
"We estimate wage and job tenure functions that include individual and firm effects capturing time-invariant unobserved worker and firm heterogeneity using German linked employer-employee data (LIAB data set). We find that both types of heterogeneity are correlated to the observed characteristics and that it is therefore warranted to include individual and firm fixed effects in both the wage and the job tenure equation. We look into the correlation of the unobserved heterogeneity components with each other. We find that high-wage workers tend to be low-tenure workers, i.e. higher unobserved ability seems to be associated with higher job mobility. At firm level, there seems to be a trade-off between wages and job stability: High-wage firms tend to be low-tenure firms, which suggests that low job stability may be compensated by higher wages. High-wage workers seem to sort into low-wage/high-tenure firms. They seem to forgo some of their earnings potential in favour of higher job stability."